Dailily cultivar Regina flowering under different NPK doses - Lopes Borduqui Cavalcante, Mateus; Alves Fogaça, Luciana (Scientia Agraria Paranaensis, 2021)
The knowledge of fertilization in ornamental plant production is essential to improve productivity and longevity of plants and their flowers. In the case of Hemerocallis x hybrida Hort. there is only few studies showing this relation. The lack of research in the field led the execution of this study, which aimed to evaluate the effect of different doses of NPK on the growth of daylily cultivar Regina. The study was conducted in an experimental area at Pontifícia Universidade Católica do Paraná, located in Toledo, PR, Brazil. Seedlings were obtained from dividing the parent plants’ clumps which were cultivated in a clonal garden. Subsequently, standardization was carried out regarding the length of the aerial part of 10 cm and root system of approximately 5 cm. The experimental design used was randomized blocks with five treatments, containing four replications with five plants each. The treatments consisted of five doses (0; 4.5; 9.0; 13.5 and 18.0 g pl-1) using NPK (4-14-8). The parameters evaluated were number of shoots per plant, number of leaves per shoot, number of stems per plant, length of stems per plant and number of flower buds per stems. We observed the flowering timing was influenced by the different doses of NPK. There was linear fit for the parameters and the dose of 18 g pl-1 promoted the best results, except for the number of stems per plant. The results indicate that increasing doses of NPK positively influence the flowering period, and promote an increase in the number of shoots, stem length and number of flower buds.